(untitled) (Fiep Bulletin - online, 2014)
The aim of this paper, which is part of the veGA 1/0759/12 project, is to analyze the motives of physical activity and barriers of non- participation in physical activities of primary school pupils according to differentiating criterion - sex. using the questionnaire we will try to defi ne the main determinants of physical activity between boys and girls, which infl uence participation in physical activities. Given to the results of the research we will suggest recommendations to eliminate physical activity barriers and support motivational elements.